1986
DOI: 10.1002/j.1551-8833.1986.tb05728.x
|View full text |Cite
|
Sign up to set email alerts
|

Removing Trace Organics by Reverse Osmosis Using Cellulose Acetate and Polyamide Membranes

Abstract: A full-scale (8-cfs [ 0.22-m3/s]) reverse osmosis (RO) water treatment plant equipped with conventional cellulose acetate membranes, and two pilot RO plants, equipped with polyamide membranes, were tested for their ability to remove total organic carbon and a broad range of trace organics, including volatiles, purgeables, neutrals, bases, phenols, and acids from lime-clarified secondary municipal wastewater. The full-scale RO system removed total organic carbon (TOC) by 89 percent to 0.95 mg/L at 84-percent wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…As reported by other researchers that, rejection of DBP compounds was influenced by compound physical chemical properties (e.g., molecular size, solubility, diffusivity, polarity, hydrophobicity, and charge), membrane properties (e.g., permeability, pore size, hydrophobicity, and charge), and membrane operating conditions (e.g., flux, transmembrane pressure, and recovery) [10,16,17,[25][26][27], both diffusion and partitioning are highly related to physical and chemical properties of compounds and membranes.…”
Section: Effects Of Transmembrane Pressures and Feed Concentrationsmentioning
confidence: 79%
See 2 more Smart Citations
“…As reported by other researchers that, rejection of DBP compounds was influenced by compound physical chemical properties (e.g., molecular size, solubility, diffusivity, polarity, hydrophobicity, and charge), membrane properties (e.g., permeability, pore size, hydrophobicity, and charge), and membrane operating conditions (e.g., flux, transmembrane pressure, and recovery) [10,16,17,[25][26][27], both diffusion and partitioning are highly related to physical and chemical properties of compounds and membranes.…”
Section: Effects Of Transmembrane Pressures and Feed Concentrationsmentioning
confidence: 79%
“…Reinhard et al stated that contaminant removal is dependent on the chemical characteristics of both membrane and contaminants [25]. Further, molecular characteristics effecting solute sorption include water solubility and hydrogen bonding ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of WF21 effluents (1979)(1980)(1981)(1982) found that none of the EPA priority pollutants were present at concentrations above Correspondence to: W.-H. Ding regulatory levels [1]. Other studies at WF21 focused on alkylphenol polyethoxylates surfactant residues, their chlorination and bromination during chlorine disinfection [2], and on removal of organics during reverse osmosis treatment [3]. Little is known about the identity and concentration of specific organics that remain after GAC contacting.…”
Section: Introductionmentioning
confidence: 96%
“…Considering that the molecular weights of almost all pesticides range from 200 to 400 Da, NF membranes are potentially useful for pesticide removal. Since NF membranes can simultaneously remove both hardness and pesticides, their application to the treatment of drinking water has been increased (Reinhard et al, 1986;Baier et al, 1987;Duranceau et al, 1992;Berg et al, 1997;Hofman et al, 1997;Van der Bruggen et al, 1998).…”
Section: Membrane Technologiesmentioning
confidence: 99%